Model Specification Searches in Structural Equation Modeling with R. Issue 3 (4th May 2018) - Marcoulides, Katerina M.; Falk, Carl F.
Abstract : This article introduces and demonstrates the application of an R statistical programming environment code for conducting structural equation modeling (SEM) specification searches. The implementation and flexibility of the provided code is demonstrated using the Tabu search procedure, although the underlying code can also be directly modified to implement other search procedures like Ant Colony Optimization, Genetic Algorithms, Ruin-and-Recreate, or Simulated Annealing. The application is illustrated using data with a known common factor structure. The results demonstrate the capabilities of the program for conducting specification searches in SEM. The programming codes are provided as open-source R functions.